Development of an alginate-Matrigel hydrogel system to evaluate cancer cell behavior in the stiffness range of the bone marrow - Northcutt, Logan A.; Questell, Alyssa M.; Rhoades, Julie; Rafat, Marjan (Frontiers in Biomaterials Science, 2023)
Bone metastasis is highly prevalent in breast cancer patients with metastatic disease. These metastatic cells may eventually form osteolytic lesions and affect the integrity of the bone, causing pathological fractures and impairing patient quality of life. Although some mechanisms have been determined in the metastatic cascade to the bone, little is known about how the mechanical cues of the bone marrow microenvironment influence tumor cell growth and invasion once they have homed to the secondary site. The mechanical properties within the bone marrow range from 0.5 kPa in the sinusoidal region to 40 kPa in the endosteal region. Here, we report an alginate-Matrigel hydrogel that can be modulated to the stiffness range of the bone marrow and used to evaluate tumor cell behavior. We fabricated alginate-Matrigel hydrogels with varying calcium sulfate (CaSO4) concentrations to tune stiffness, and we demonstrated that these hydrogels recapitulated the mechanical properties observed in the bone marrow microenvironment (0.7 kPa to 16 kPa). We encapsulated multiple breast cancer cell lines into these hydrogels to assess growth and invasion. Tumor cells in stiffer hydrogels exhibited increased proliferation and enhanced elongation compared to lower stiffness hydrogels, which suggests that stiffer environments in the bone marrow promote cellular invasive capacity. This work establishes a system that replicates bone marrow mechanical properties to elucidate the physical factors that contribute to metastatic growth.